Implementation Of Marker-Based Tracking Method On Augmented Reality In Multimedia Learning (Case Study Of STMIK Tegal) (Buana Information Technology and Computer Sciences (BIT and CS), 2024)
Introducing campus locations for new students or address seekers is an important activity. Multimedialearning is not only a tool for creating harmonious presentations and alternatives that combine visualand audio media; technology can be used for its tools. Augmented Reality (AR) is one of them.Augmented Reality is helpful as a combination of virtual and Reality devices that operate interactivelyin a realtime natural environment. Based Marker Tracking is a method used to make objects into twodimensions and three dimensions whose process begins with directing the marking object by the userusing the camera on the mobile device until the camera reads the object. Light intensity affects detectionsuccess, and distance calculation also becomes essential. If the marker is successfully detected, theapplication will convert it into a 3-dimensional object as the final result. In this study, a location searchwill be carried out for the STMIK TEGAL Campus Building using Augmented Reality based on theBased Marker Tracking method to produce the most ideal conditions to be able to display 3D objectsfrom the STMIK TEGAL Building, which is a distance of 15 to 25 cm with bright Light using Android,so that this application can be used to find the location of the STMIK TEGAL Building.